2022
DOI: 10.3389/fpsyg.2022.1064898
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the role of family support, coping strategies and social support in improving the mental health of students: Evidence from post COVID-19

Abstract: BackgroundThe COVID-19 pandemic and the multifaceted response strategies to curb its spread both have devastating effects on mental and emotional health. Social distancing, and self-isolation have impacted the lives of students. These impacts need to be identified, studied, and handled to ensure the well-being of the individuals, particularly the students.AimThis study aims to analyze the role of coping strategies, family support, and social support in improving the mental health of the students by collecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 61 publications
2
7
0
1
Order By: Relevance
“…The TCEs from all four ethnicities expressed that talking with their loved ones on video and phones allowed them to feel comfort and ease. This is analogous to the research by Yang et al [ 80 ] that examined the role of coping tactics in the promotion of psychological well-being during the pandemic. The results of the study suggested that family support is positively associated with better mental states [ 80 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The TCEs from all four ethnicities expressed that talking with their loved ones on video and phones allowed them to feel comfort and ease. This is analogous to the research by Yang et al [ 80 ] that examined the role of coping tactics in the promotion of psychological well-being during the pandemic. The results of the study suggested that family support is positively associated with better mental states [ 80 ].…”
Section: Discussionsupporting
confidence: 68%
“…This is analogous to the research by Yang et al [ 80 ] that examined the role of coping tactics in the promotion of psychological well-being during the pandemic. The results of the study suggested that family support is positively associated with better mental states [ 80 ]. Subsequently, an interpretative phenomenological analysis was conducted by Xiuxiang et al [ 81 ] to assess the coping strategies of 14 family caregivers in China.…”
Section: Discussionsupporting
confidence: 68%
“…The median of PTSS was 24 (IQR, [19][20][21][22][23][24][25][26][27][28][29][30][31][32], ranging from 17 to 85. According to the critical value of PCL-C in the screening for PTSS [30], 230 medical students had PTSS among 2208 medical students.…”
Section: Status Of Post-traumatic Stress Symptomsmentioning
confidence: 99%
“…A study indicated that family support and coping strategies are closely related to mental health. Coping strategies play a mediating role between family support and mental health during the COVID-19 pandemic [ 20 ]. Research on patients with cured COVID-19 showed that emotional support was a protective factor against PTSD [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A sense of social status in one's community often reflects a level of community connectedness that may confer these benefits as well. In these ways, social status and support can be directly beneficial to the health of racial/ethnic minorities navigating the challenges of the pandemic (20,49). Strengths of our study include a large dataset covering a wide range of participants across race/ethnicity, gender, and age.…”
Section: Discussionmentioning
confidence: 99%